Preventing the resource curse? : an examination of the Chad-Cameroon Pipeline Project - Harry, Priya (Department of Political Studies, 2014)
The resource curse is a theory which argues that rather than being a conduit for development natural resources can in fact lead to slow growth, civil war and hinder democracy. This thesis focuses specifically on the inverse relationship between dependence on the export of natural resources and slow economic growth, and how to prevent it.